Videolaryngoscopy: a help or a hindrance?. (2nd October 2021) - Stokes, Victoria; Dearden, Luke; Martin, Andrew
Abstract : Airway management is fundamental to anaesthesia, and technology may help with the safety of this procedure. Videolaryngoscopy is a developing area, which is becoming commonplace in anaesthesia practice.